L' Etat Moderne. (Paris, 1932)
Bibliotheek E. Anseele
Motto: Indépendance, technicité, collaboration, réalisation
Periodiciteit: maandelijks
Hoofdredactie: rue Marsollier 11, Paris-2e
Medewerkers: E. Poisson, A.J. Cleuet, Emile Bugnon, Gaston Lévy, René Vaxelaire, Jean Gaumont, G. Fauquet, Gaston Prache, A. Daudé-Bancel, Georges Gaussel, Paul Allard
Beheer/Administratie: Albert Plantier (gérant), rue Marsollier 11, Paris 2e
Drukker/Drukkerij: Imprimerie Les Presses Modernes, rue de Mauberge 45, Paris